2007
DOI: 10.1111/j.1741-3737.2006.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended Family Integration Among Euro and Mexican Americans: Ethnicity, Gender, and Class

Abstract: This article compares the extended family integration of Euro and Mexican American women and men and assesses the importance of class and culture in explaining ethnic differences. Using National Survey of Families and Households II data (N = 7,929), we find that ethnic differences depend on the dimension of integration. Mexican Americans exhibit higher rates of kin coresidence and proximity, but lower rates of financial support than Euro Americans. Two additional differences exist only among women: Mexican Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 33 publications
4
105
0
1
Order By: Relevance
“…These grandparents may be more likely to have fewer resources, which may become further strained in the face of earlier morbidity. Non-Hispanic black and Hispanic grandparents are more likely to provide in-kind transfers, such as childcare and practical support, than nonHispanic white grandparents (Sarkisian and Gerstel 2004;Sarkisian et al 2007), and earlier declining health of these grandparents may reduce their ability to contribute to younger generations earlier than white and more highly educated grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…These grandparents may be more likely to have fewer resources, which may become further strained in the face of earlier morbidity. Non-Hispanic black and Hispanic grandparents are more likely to provide in-kind transfers, such as childcare and practical support, than nonHispanic white grandparents (Sarkisian and Gerstel 2004;Sarkisian et al 2007), and earlier declining health of these grandparents may reduce their ability to contribute to younger generations earlier than white and more highly educated grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a study on battered Mexican women show that participants perceive family, friends, and other informal support sources as more accessible than formal support (Fawcett et al,1999). Another study comparing Mexican-American and Anglo extended family integration found that the former group reported higher rates of closeness and informal support from their families (Sarkisian, Gerena, & Gerstel, 2007).…”
Section: Cultural Factorsmentioning
confidence: 96%
“…Actual and perceived parental support for young adults depends on children’s needs and social roles and parent characteristics and resources (Fingerman et al 2009; Mazelis and Mykyta 2011; Sarkisian, Gerena, and Gerstel 2007; Swartz et al 2011), and these factors may be associated with immigrant status and racial/ethnic identity. We discuss the prior literature on parental support for young adult children generally, before turning to specific considerations in immigrant and minority families.…”
Section: Factors Influencing Parental Supportmentioning
confidence: 99%